VARENICLINE IN PATIENTS WITH CARDIOVASCULAR DISEASES - FRIEND OR ENEMY? - Yu. V. Lukina; S. Yu. Martsevich (Столичная издательская компания, 2015)
The problem of varenicline use in patients with cardiovascular diseases is discussed. Results of large clinical trials and meta-analyses with varenicline have proven its high efficacy for treatment of nicotine addiction in adults and a small number of side events. Varenicline is the main agent for pharmacotherapy of nicotine addiction due to its high efficacy and advantages of smoking cessation. However careful monitoring of its side effects is needed in these patients.